Promoting highly dispersed Co3O4 nanoparticles onto polyethyne unraveling the catalytic mechanism with stable catalytic activity for oxygen evolution reaction: From fundamentals to applications. (14th October 2021) - Mugheri, Abdul Qayoom; Samtio, Muhammad Soomar; Sangah, Ali Asghar; Awan, Jawad Hussain; Memon, Shahzad Ahmed
Abstract: The solution to overcome the energy crisis in the globe with saving the environment from pollution and the community health, along with other applications of electrochemical for water splitting to get hydrogen and oxygen as a clean fuel. Likewise, the conducting polymers experience as stability over long time, or some time the breaking of conducting polymer chain is unavoidable with addition of polymer. For many reasons, we use noble metal co-catalysts in conjunction with semiconductors for improved hydrogen and oxygen gas production by the water splitting. The morphological characterization, & chemical composition of pristine & composite material studies with the help of different analytical techniques as like SEM, EDX, XRD, XPS & HRTEM. An outperform and active non-noble electrocatalyst for the oxygen evolution reaction which is a hotspot in the current research activities for oxygen & hydrogen production with zero carbon dioxide emission. Herein, we present an advanced material Co3 O4 /polyethyne for the first time to produce oxygen at a reasonable overpotential. The best oxygen evolution performance of Co3 O4 /polyethyne (20) providing the best performance at low overpotential 260 mV at 10 mAcm −2 the Tafel slope 64 mVdec −1, further strongly acceptable durability approximately for the 30 h & finally obtained charge transfer resistance value of 82.58 Ohms & greater capacitance 1.56 mF value for Co3 O4 . The key element in the success of newly developed catalyst is the greater amount of Co3 O4 nanoparticles due to selective growth on polyethyne which has played a dominant role in oxygen production. It is because of the worth mentioning properties of polyethyne as a good electrical conductor, as efficient catalyst Co3 O4 with more surface roughness and high surface area, which is strongly boosting the production of oxygen. The developed material can be applied in other competing fields such as lithium-ion batteries, solar cells, energy storage devices, and photochemical water splitting. Highlights: Oxygen is a hopeful, ideal cost-efficient, clean, and sustainable energy carrier. The composite achieves a current density of 10 mA/cm 2 at overpotential of 260 mV & obtained Tafel slope of 64 mVdec −1 . The chronopotentiometry shows that catalyst is highly durable for 30 h in basic media. Co3 O4 can potentially Promising achievements are catalysis, for water splitting.